Difference between revisions of "Proportion/Intermediate"
(source) |
|||
(One intermediate revision by one other user not shown) | |||
Line 3: | Line 3: | ||
==Solution== | ==Solution== | ||
− | {{ | + | |
+ | First, let's write these out algebraically: the first is <math>x=k(y^2+z^2)</math>, the second is <math>xy=k_1</math>, and the third is <math>xz^2=k_2</math>. Plugging the values into the first equation gives <math>8=k((\frac{1}{2})^2+(\frac{\sqrt{3}}{2})^2)=k(\frac{1}{4}+\frac{3}{4})=k</math>, so <math>k=8</math>. The second gives <math>8*\frac{1}{2}=4=k_1</math>, and the third gives <math>8*(\frac{\sqrt{3}}{2})^2=8*3/4=6=k_2</math>. We can use any of these three to solve the problem. Using the second gives us <math>1*y=y=4</math>, so the answer is <math>y=4</math>. | ||
+ | |||
+ | [[Category:Intermediate Algebra Problems]] |
Latest revision as of 13:24, 26 February 2013
Problem
is directly proportional to the sum of the squares of
and
and inversely proportional to
and the square of
. If
when
and
, find
when
and
. (Thanks to Bicameral of the AoPS forum for this one)
Solution
First, let's write these out algebraically: the first is , the second is
, and the third is
. Plugging the values into the first equation gives
, so
. The second gives
, and the third gives
. We can use any of these three to solve the problem. Using the second gives us
, so the answer is
.